Unequal causality between autoimmune thyroiditis and inflammatory bowel disease: a Mendelian randomization study - Bai, Siyang; Yu, Yunfeng; Yang, Xinyu; Hu, Gang; Wu, Jingyi; Tong, Keke; Yin, Yuman; Deng, Juan; Chen, Cong; Tan, Chuanchuan (Frontiers in Endocrinology, 2024)
Objective: This study aims to analyze the causal relationship between autoimmune thyroiditis (AIT) and inflammatory bowel disease (IBD) using bidirectional Mendelian randomization (MR). Methods: Single nucleotide polymorphisms were obtained from FinnGen. Exposure-outcome causality was assessed using inverse variance weighted, MR-Egger, and weighted median. MR-Egger intercept, Cochran’s Q, and leave-one-out sensitivity analysis were used to evaluate horizontal pleiotropy, heterogeneity, and robustness, respectively. Results: Forward analysis revealed no significant association between AIT and the risk of ulcerative colitis (UC) (odds ratio [OR] 1.008, 95% confidence interval [CI] 0.986 to 1.03, p = 0.460) or Crohn's disease (CD) (OR 0.972, 95% CI 0.935 to 1.010, p = 0.143). Reverse analysis showed that UC (OR 0.961, 95% CI 0.783 to 1.180, p = 0.707) was not associated with AIT risk, while CD (OR 2.371, 95% CI 1.526 to 3.683, p < 0.001) was linked to an increased risk of AIT. Intercept analysis and Cochran’s Q test indicated no horizontal pleiotropy or heterogeneity. Sensitivity analysis confirmed the robustness of the MR results. Conclusion: This MR analysis suggests that CD, but not UC, is a risk factor for AIT, whereas AIT is not associated with the risk of IBD. Proactive prevention and treatment of CD can help mitigate the risk of AIT.